Proceedings of the Ninth International Workshop on Natural Language Processing for Social Media 2021
DOI: 10.18653/v1/2021.socialnlp-1.4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of COVID-19 on Restaurant Reviews

Abstract: The COVID-19 pandemic has implications beyond physical health, affecting society and economies. Government efforts to slow down the spread of the virus have had a severe impact on many businesses, including restaurants. Mandatory policies such as restaurant closures, bans on social gatherings, and social distancing restrictions have affected restaurant operations as well as customer preferences (e.g., prompting a demand for stricter hygiene standards). As of now, however, it is not clear how and to what extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The COVID-19 pandemic created many complications beyond the spread of viruses and food-borne illnesses that have affected physical health. Thus, it is very important for governments to control the spread of the virus by implementing strict rules regarding public gatherings, especially in restaurants and other foodservice establishments [39]. It is notable that the current study showed that a significant proportion of employees at foodservice establishments did not believe that these restrictions and regulations improved food safety conditions and they had not noticed any improvements regarding food safety in their establishments since the pandemic began.…”
Section: Discussionmentioning
confidence: 60%
“…The COVID-19 pandemic created many complications beyond the spread of viruses and food-borne illnesses that have affected physical health. Thus, it is very important for governments to control the spread of the virus by implementing strict rules regarding public gatherings, especially in restaurants and other foodservice establishments [39]. It is notable that the current study showed that a significant proportion of employees at foodservice establishments did not believe that these restrictions and regulations improved food safety conditions and they had not noticed any improvements regarding food safety in their establishments since the pandemic began.…”
Section: Discussionmentioning
confidence: 60%
“…We model the expected WELLBEING of a city's subreddit using the Prophet model (Taylor and Letham 2018) trained on data prior to March 2020 (Jan. 1, 2017-Feb. 29, 2020; this model has been used in prior work on the impacts of COVID-19 on social media forums (Biester et al 2021;Cao et al 2021). The model fits the equation…”
Section: Measuring Resiliencementioning
confidence: 99%
“… Jia (2021) indicated that customers become calm when they are in line, a situation that causes a negative influence in normal periods. Cao et al (2021) extracted 3.1 million online reviews, utilized methods of sentiment analysis and topic modeling, and discovered that more than 10% of online reviews included COVID-associated keywords and that the prevalence of COVID-associated factors (e.g., mask, social distancing, and hygiene) raised during the COVID-19 pandemic, while the prevalence of other factors decreased. Luo and Xu (2021) analyzed 112,412 Yelp reviews posted during the crisis by applying methods of sentiment analysis and keyword analysis.…”
Section: Literature Reviewmentioning
confidence: 99%